The Commodification of History: Debunking Processes of Authenticity and Simulacra in Julian Barnes’ England, England 1999. - Rabia ZIANI; Abbes BAHOUS (Altralang Journal, 2023)
Englishness has become a focal point of research and exploration, placing itself at the heart of debates within contemporary literary criticism. In this article, I will be taking Julian Barnes‘ England, England 1999 as a case study to highlight the workings of the aspects of authenticity and simulacra by attempting to break down the mechanisms that contribute to the rebranding of national identity as well as presenting an account of postmodern reflections of the novel. I also try to highlight the obvious influence of the author by French elements in terms of form and technique.  My research touches upon the unreliability of memory, historical commodification and narrative techniques of perspectivation and characterisation amongst others, in order to showcase how Barnes manages through the amalgamation of particular techniques to denounce the artificiality of authenticity as a whole, and in focus, that of Englishness.